Analisis Peningkatan Kinerja dan Umur Pahat Karbida Pada Proses Pembubutan Baja Aisi 1045 dengan Menggunakan Coating Tialn - Laurenzo, Michael; Lubis, Sobron Yamin; Rosehan, Rosehan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Lathe is a machine tool that is used to cut the object being rotated. Lathe itself is a workpiece cutting process in which the incision is made by rotating the workpiece and then being applied to the tool which is moved translationally with the rotary axis of the workpiece. In this study the method used was an experimental research method consisting of TiAlN coating to turning process. The results showed that the cutting speed is inversely proportional to the life of the tool, where the higher the cutting speed, the shorter the life of the tool. The higher the cutting speed, the lower the surface roughness value. TiAlN coating has a significant effect on the surface quality of the workpiece and the life of the tool, where the TiAlN coating has a lower surface roughness value than the tool without coating at the same cutting speed.